2000
DOI: 10.4088/pcc.v02n0502
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Abuse and Psychiatric Side Effects

Abstract: Methylphenidate is a central nervous system stimulant drug that has become the primary drug of choice in treating attention-deficit/hyperactivity disorder in children. Side effects are usually mild and are generally well tolerated by patients. Along with increases in prescribing frequency, the potential for abuse has increased. Intranasal abuse produces effects rapidly that are similar to the effects of cocaine in both onset and type. The clinical picture of stimulant abuse produces a wide array of psychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(139 citation statements)
references
References 47 publications
0
129
1
9
Order By: Relevance
“…Its known addictive potential, which is linked to its dopaminergic action, documented by both animal and clinical studies, [1,2] has in France led to its classification as a psychoactive drug, dispensed via secure prescription for a limited period of 28 days. It is also subject to a once-yearly hospital prescription (restricted to specialists and departments of neurology, paediatrics, psychiatry and sleep centres).…”
Section: Introductionmentioning
confidence: 99%
“…Its known addictive potential, which is linked to its dopaminergic action, documented by both animal and clinical studies, [1,2] has in France led to its classification as a psychoactive drug, dispensed via secure prescription for a limited period of 28 days. It is also subject to a once-yearly hospital prescription (restricted to specialists and departments of neurology, paediatrics, psychiatry and sleep centres).…”
Section: Introductionmentioning
confidence: 99%
“…Em 1958, na antiga União Soviética, ocorre a primeira faloplastia (cirurgia de construção de um pênis a partir de enxertos de tecidos de pele), parte do processo de mudança de sexo de mulher para homem (Preciado, 2008) (Morton, Stockton, 2000). Vemos nascer uma sociedade na qual a presença e a utilização de drogas dos mais diferentes tipos fazem parte tanto da vida de uma atleta, quanto de pessoas em tratamentos médicos convencionais.…”
Section: Da Manipulação Dos Hormônios Ao Doping Esportivounclassified
“…12 Methylphenidate is used for ADHD patients and also abused nowadays; it has been shown to induce clinical psychosis apart from other neuropsychiatric symptoms as adverse effects. 14 It has also been shown previously that when used between doses of 10-30 mg/kg body weight in rodents, mmethylphenidate promotes a dose dependent behavioural profile that is very comparable to that of amphetamine. 13 In this study by Kuczenski and Segal, methylphenidate promoted a dose-dependent pattern of locomotion and stereotypy similar to results with amphetamine in previous studies.…”
Section: Methylphenidate As a Model For Psychosis (Stereotypy)mentioning
confidence: 99%
“…Its proposed mechanism of action is the release and increase of CNS dopamine .This release is secondary to its effect on the dopamine transport mechanism, which results in an increased amount of postsynaptic dopamine. 14 We found in a pilot study that methylphenidate showed significant stereotypy at dose of 5 mg/kg itself. So we decided to use this dose of methylphenidate and could find significant characteristic stereotypy behavior (sniffing, gnawing, paw licking) and also a hyper locomotion response.…”
Section: Methylphenidate As a Model For Psychosis (Stereotypy)mentioning
confidence: 99%